RLIP76, an effector of the GTPase Ral, interacts with the AP2 complex: involvement of the Ral pathway in receptor endocytosis. - Jullien-Flores, V.; Mahe, Y.; Mirey, G.; Leprince, C.; Meunier-Bisceuil, B.; Sorkin, A.; Camonis, J.H. (Journal of Cell Science, 2000)
RLIP76 is a modular protein that was identified as a putative effector of Ral, a GTPase activated during Ras signaling. To explore further the contribution of the Ral-RLIP76 pathway to Ras signaling, we have looked for partners of RLIP76. Mu2, the medium chain of the AP2 complex is shown to interact with RLIP76. We show also that in vivo endogenous AP2 and RLIP76 form a complex and that this in vivo interaction is independent of cells being stimulated by a growth factor. Furthermore, RLIP76 differentiates AP2 from AP1 in vivo as RLIP76 differentiates mu2 from mu1 in vitro and in two hybrid assays. We show that activated Ral interferes with both tranferrin receptor endocytosis and epidermal growth factor (EGF) receptor endocytosis in HeLa cells. We propose a model where the Ral-RLIP76 pathway connects signal transduction and endocytosis through interaction on one hand between the Ras-Ral pathway and RLIP, on the other hand between RLIP and proteins belonging to the endocytotic machinery.